Memories of school recess predict physical activity enjoyment and social-emotional well-being in adults. (July 2021) - Massey, William V.; Szarabajko, Alexandra; Thalken, Janelle; Perez, Deanna; Mullen, Sean P.
Abstract: School recess can provide social, emotional, and physical benefits for children. Yet, not all children experience recess the same, as inequity in access to recess and variability in the quality of recess exist. Researchers have yet to understand the long-term implications of recess experiences on adult well-being and physical activity behaviors. The purpose of this study was to explore the inter-relationships between memories of recess, physical activity, and social-emotional well-being. A total of 514 adults between the ages of 19 and 79 ( M = 45.56; SD = 15.62) were surveyed via Prolific, a web-based research platform. Participants were asked about their memories of recess enjoyment and recess exclusion, and current physical activity levels, physical activity enjoyment, social isolation, social role satisfaction, and sense of meaning and purpose. Structural equation modeling analysis showed that memories of recess enjoyment were associated with meaning and purpose ( β = 0.138, p < .05) and PA enjoyment ( β = 0.183, p < .05). Furthermore, retrospective recess exclusion predicted current social isolation ( β = 0.266, p < .05) and was negatively associated with retrospective recess enjoyment ( β = −0.379, p < .05). Findings highlight the importance of childhood recess experiences and its impact on current physical activity behaviors, social isolation, and meaning and purpose later in life. Consistent with other research, early positive physical activity experiences, in the form of recess, appear to provide more assurances that one will engage in healthier lifestyle behaviors and more favorable psycho-socio-emotional profiles in adulthood. Highlights: Memories of recess exclusion was associated with social isolation in adulthood. Memories of recess enjoyment was associated with meaning and purpose in adulthood. Memories of recess enjoyment was associated physical activity enjoyment in adulthood. Recess had an indirect effect on adult physical activity via physical activity enjoyment.